(untitled) (Studia Prawnicze / The Legal Studies, 1983)
The article is based on the investigation carried out in 1976 on the Polish:; population by the Polish Radio and Television Centre of Public Opinion and Broadcasting Research. The article presents the opinions of people investigated on the following questions: the main purpose of imprisonment, censorship of mail and control of visits: in prison, the future of imprisonment as punishment, are we to limit its usage, are we to loosen, to tighten, or to keep unchanged the restrictions imposed on priseners, attitudes to former prisoners. The analysis of the results of the research leads to the conclusion that as. far as the above mentioned problems are concerned the Polish population shows a relatively high degree of rigour and conservatism. The author doubts whether-the society can play an active role in the process of resocialization. The author postulates to disseminate information about man violating social rules, about factors leading to the commission of a crime, about negative results of imprisonment and about the most recent achievements in the penitentiary field